Pelatihan Table Manners Mahasiswa Politeknik Darussalam - Dwi Hanadya; Ariya Agustin; Nyayu Ully Auliana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of this training is to provide valuable experience as well as useful knowledge for Darussalam Polytechnic students. The table manners activity is the main provision for students when they have finished studying at the Darussalam Polytechnic. The participants of this training were 108 students from all majors in Darussalam Polytechnic. This training was held at Fave Hotel Palembang on March 31, 2022. The speakers in this training were lecturers from the Travel Business Department who were competent in the field of hospitality and tourism. In this training, it is emphasized how to use good etiquette in eating. Eating etiquette which is manners at banquets. Dining etiquette at the dining table is quite simple, but there are some things that can be learned in how to sit up straight and don't lean on the back of the chair, and don't put your elbows on the dining table and use a napkin on your lap. Banquets are not just how to put food in the mouth, but are related to certain eating etiquette that can show a person's personality. Manners at the dinner table really need to be learned by Darussalam Polytechnic students so that they can have skills in good eating procedures at the dinner table, starting with how to proceed at the dinner table by doing table manners training.